Pembubaran Organisasi Kemasyarakatan Perspektif Siyasah Syar’iyyah dan Negara Hukum - Nabih Amer; Rahmat Teguh Santoso Gobel (Al-Mizan (e-Journal), 2019)
This article discusses the problem of the dissolution of social organizations in Indonesia that is not in accordance with the principles of the rule of law. These problems will be answered methodologically using normative legal research. The author uses this legal research because the focus is on studying literature, legislation and court decisions relating to the object of research. Based on the results of the study this article concludes that the 1945 Constitution of the Republic of Indonesia emphasizes the importance of a system of checks and balances in which there needs to be a clear division of power between the executive and judicial functions. This means that in the case of the dissolution of social organizations it is very important to involve the court in deciding the dissolution of the social organization in Indonesia by structuring dispute resolution in the courts using the principle of quick, simple and low cost justice so that the process of dispute resolution of the social organization can be carried out effectively and efficiently.